Measuring Constitutional Loyalty: Evidence from the Covid-19 Pandemic - Jerg Gutmann; Roee Sarel; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2022)
Constitutional loyalty, the importance ascribed to complying with constitutional rules, is difficult to measure across countries due to differences in context, history, and culture. We overcome this challenge by exploiting the COVID-19 pandemic as an ideal setting in which societies around the world face a novel and similar public health crisis, inducing governments to adopt comparable policies. Based on a survey carried out in 53 countries around the world in 2021, we show that citizens' support for Covid-19 mitigation policies declines if courts signal doubts about their constitutionality. We further demonstrate that this effect of constitutional loyalty depends on citizens' characteristics, such as their confidence in the courts and their moral convictions.
Keywords: D02; H12; I18; K40; P48; 330; Constitutional loyalty; Constitutions; Courts; Covid-19; Judicial power